SPATIAL-TEMPORAL DYNAMICS OF LITTORAL ZOOPLANKTON COMMUNITY OF THE OLEKSANDRIVKA RESERVOIR - V. Trokhymets (Vìsnik: Kiïvsʹkij Nacìonalʹnij Unìversitet Imenì Tarasa Ševčenka. Bìologìâ, 2017)
The analysis results of spatio-temporal dynamics of zooplankton communities from littoral of the Oleksandrivka reservoir are presented. The features of the seasonal changes in species composition, faunal and ecological spectrums, quantitative indicators (density and biomass) and the dominant species complexes of littoral zooplankton was revealed. The analysis of seasonal dynamics of qualitative and quantitative development of zooplankton in the littoral zone within the upper, middle and lower parts of the Oleksandrivka reservoir was conducted.